Polygamy slows diversification in shorebirds_rawdata - D'Urban Jackson, Josephine Anne; Dos Remedios, Natalie; Maher, Kathryn H.; Zefania, Sama; Haig, Susan; Oyler-McCance, Sara; Blomqvist, Donald; Burke, Terry A.; Bruford, Mike; Szekely, Tamas; Küpper, Clemens (Dryad Digital Repository, 2017)
This file contains all of the raw microsatellite data for ten species of plover. Kittlitz's plover and white-fronted plover are divided into two datasets which represent 1) mainland African populations and 2) Madagascan populations. Details of the microsatellite markers and PCR conditions can be found in the paper. Killdeer plover has one marker identified as having a high estimate of null alleles, this is marked in grey shading.